Strategizing pigeonpea for enhancing health-benefitting traits: A path to nutritional advancements - Jwala Pranati; Vaishnavi Chilakamarri; Ashwini Kalyan; H.B. Shruthi; Naresh Bomma; Kalenahalli Yogendra; Prakash Gangashetty (Crop Design)
Nutritional security is the key objective of India's 2030 Vision and UN Sustainable Development Goal 3. Although great progress has achieved towards food security, it is vitally important to solve protein- energy malnutrition and micronutrient deficiencies for millions of people worldwide providing by providing nutrient-rich foods a long-term solution. Pigeonpea is a major daily diet of developing and undeveloped nations covering Asian and African households, and increasing its protein and micronutrient (iron and zinc content) is a feasible approach. Thus, this review focusses on strategizing how pigeonpea should provide nutritional assurance in the coming decade. we primarily summarizes the dietary profile, health advantages, and anti-nutritional factors that hinder pigeonpea. Furthermore, current progress through conventional breeding and molecular tools was comprehensively discussed, while providing strategies to amalgamate advances in transgenics, omics and rapid generation advancement platforms to enhance health-benefitting traits and tackling the anti-nutritional factors contributing potentially towards the nutritional security of pigeonpea food.